Harnessing exception: Mobilities, credibility, and the casino. (June 2016) - Zhang, Juan; Yeoh, Brenda SA
Using Singapore's newly opened mega casino resorts as an example, this article illustrates how the expanding casino economy in Asia shapes, and is shaped by, an emerging mobility regime that works through the politics of exception. The coupling of mobility and exception creates a particular governing technology of tracking credibility through which mobile subjects and citizen subjects become manageable. Credibility demands that individuals must demonstrate their own rationality and capability in the exceptional space of global circulation. Exception is harnessed when logics of economic optimization and ethicalization are maintained to legitimize different processes of channeling, sorting, and bordering. They create new articulations of mobile identities and exclusion.